2014
DOI: 10.1371/journal.pone.0113531
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Effects of Aged Garlic Extract and Its FruArg Component on Lipopolysaccharide-Induced Neuroinflammatory Response in Microglial Cells

Abstract: Aged garlic extract (AGE) is widely used as a dietary supplement, and is claimed to promote human health through anti-oxidant/anti-inflammatory activities with hypolipidemic, antiplatelet and neuroprotective effects. Prior studies of AGE have mainly focused on its organosulfur compounds, with little attention paid to its carbohydrate derivatives, such as N-α-(1-deoxy-D-fructos-1-yl)-L-arginine (FruArg). The goal of this study is to investigate actions of AGE and FruArg on antioxidative and neuroinflammatory re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 53 publications
2
26
0
Order By: Relevance
“…Nitrosative stress elicited by NO and RNS has been implicated in the pathogenesis of neurodegenerative diseases, such as AD, Parkinson's disease and traumatic brain injury (TBI) (47-52). Previous studies by our group demonstrated that AGE can attenuate NO production in microglial BV-2 cells (20,21). Specifically, treatment with AGE (0.1-1%) or FruArg (2-5 mM) for 20 h was found to significantly reduce NO production in a dose-dependent manner in BV2 cells against LPS-induced neuroinflammation (20).…”
Section: Neuroprotective Effects Of Agementioning
confidence: 79%
See 2 more Smart Citations
“…Nitrosative stress elicited by NO and RNS has been implicated in the pathogenesis of neurodegenerative diseases, such as AD, Parkinson's disease and traumatic brain injury (TBI) (47-52). Previous studies by our group demonstrated that AGE can attenuate NO production in microglial BV-2 cells (20,21). Specifically, treatment with AGE (0.1-1%) or FruArg (2-5 mM) for 20 h was found to significantly reduce NO production in a dose-dependent manner in BV2 cells against LPS-induced neuroinflammation (20).…”
Section: Neuroprotective Effects Of Agementioning
confidence: 79%
“…Previous studies by our group also demonstrated the ability of both AGE and FruArg to reduce nitric oxide (NO) production in lipopolysaccharide (LPS)-stimulated murine microglial BV-2 cells in a concentration-dependent manner (20,21). Subsequently, we applied quantitative proteomic analysis by two-dimensional differential in-gel electrophoresis (2D-DIGE) integrated with liquid chromatography tandem mass spectrometry (LC-MS/MS) to profile the proteome patterns and to determine the effects of AGE and FruArg on LPS-stimulated BV-2 cells (20). Furthermore, we investigated gene regulation and associated signaling pathways using the RNA-sequencing (RNA-Seq) approach coupled with machine learning based bioinformatics analysis (21).…”
Section: Bioactive Components From Garlic On Brain Resiliency Againstmentioning
confidence: 86%
See 1 more Smart Citation
“…Z-ajoene from garlic exerted neuroprotective effects by reducing lipid peroxidation and antioxidant or anti-inflammatory activities [37]. A few other clinically proven neuroprotective agents from garlic are S-propargylcysteine and S-methyl cysteine and N-α-(1-deoxy-D-fructos-1yl)-L-arginine [38,39].…”
Section: Neuroprotective Effectmentioning
confidence: 99%
“…29,30 In our previous study, both AGE and FruArg exhibited a capability to modulate neuroinflammatory responses by suppressing nitric oxide (NO) production, in a concentration-dependent manner, in lipopolysaccharide-induced mouse BV-2 microglial cells without affecting the cell viability. 31 This result has thus created a pretext for further studies aiming to evaluate the potential of AGE and FruArg in targeting neuroinflammation in vivo.…”
Section: Introductionmentioning
confidence: 99%